Influence of Cytokine Genetic Polymorphisms in Helicobacter pylori-Associated Gastric Inflammation According to Sex in South Korea - Hee Jin Kim; Nayoung Kim; Jae Young Jang; Sihyun Kim; Jongchan Lee; Hyeon Jeong Oh (Gut and Liver)
Background/Aims: The relationship between genetic polymorphisms and gastric inflammation remains unclear. This study aimed to evaluate the impact of genetic polymorphisms on Helicobacter pylori (HP)-associated gastritis according to sex. Methods: Two hundred thirty-two male and 404 female subjects with current HP infection were prospectively enrolled. The genotyping of IL-1B-511 C/T, IL-1RN variable number of tandem repeats, IL-6-572 G/C, IL-8-251 A/T, IL-8-781 C/T, IL-10-1082 G/A, IL-10-592 C/A, TNF-A-308 G/A, and transforming growth factor (TGF)-B-509 C/T, was determined by polymerase chain reaction-restriction fragment length polymorphism. The degree of monocyte or neutrophil infiltration, atrophic gastritis, and intestinal metaplasia was evaluated using the updated Sydney system. Results: Among the male subjects, moderate/severe atrophic gastritis of the corpus was higher in IL-1B-511 CC carriers than in CT and TT carriers independent of age, alcohol consumption, and HP virulence factors (26.9% vs 10.4%; adjusted hazard ratio [HR], 4.377; 95% confidence interval, 1.387 to 13.814). In females, IL-8-251 AA carriers were independently and significantly associated with moderate/severe atrophic gastritis of the corpus compared with that in AT and TT carriers (21.4% vs 6.0%, adjusted HR=3.799). In males, the IL-8-251 TT genotype was associated with moderate/severe intestinal metaplasia of the corpus compared with the AT and AA genotypes (13.4% vs 5.6%, adjusted HR=3.128), while the IL-10-592 CA and CC genotypes were associated with moderate/severe monocyte infiltration of the antrum compared with AA genotype (83.6% vs 71.8%, adjusted HR=2.227). Conclusions: Genetic polymorphisms in cytokines play different roles in HP-associated gastritis according to sex.